Enhanced humidity pockets originating in the mid boundary layer as a mechanism of cloud formation below the lifting condensation level - Eitan Hirsch; Ilan Koren; Orit Altaratz; Zev Levin; Eyal Agassi (Environmental Research Letters, 2017)
A ground-based field campaign was conducted during the summer of 2011, 10 km east of the Israeli coast, aimed at studying small, warm convective clouds. During the campaign, clouds were detected on days that were predicted to be cloud-free by standard forecasting methods. Moreover, the clouds’ bases were often much lower than the estimated lifting condensation level. Detailed air parcel model simulations revealed that such small non-buoyant clouds can form only if the convective motion is driven by perturbations in the relative humidity in the middle of the boundary layer, rather than by temperature perturbations near the surface. Furthermore, cloud base height exhibited weak sensitivity to the initial elevation of the parcel, suggesting that it serves as an accumulation point for many relative-humidity-perturbed thermodynamic trajectories. Such a mechanism is likely to be common under atmospheric conditions of a hot and humid boundary layer capped by a strong inversion layer.